2010
DOI: 10.1016/j.jns.2010.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenology and anatomy of abnormal behaviours in primary progressive aphasia

Abstract: Primary progressive aphasia (PPA) is a group of disorders with progressive language impairment. Abnormal behaviour may develop in PPA as the disease evolves, but the clinical features and brain basis of behavioural change in PPA have not been fully defined. 33 PPA patients (9 semantic dementia, SD, 14 progressive nonfluent aphasia, PNFA, 7 logopenic/phonological aphasia, LPA and 3 patients with a PPA syndrome in association with progranulin mutations, GRN-PPA) were assessed using the Neuropsychiatric Inventory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
105
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 112 publications
(115 citation statements)
references
References 31 publications
6
105
1
3
Order By: Relevance
“…44 Moreover, the significant thinning of the orbitofrontal and premotor areas, which we found to correlate with ALSFRS-R and disease duration, may reflect a similar cortical degeneration pattern reported in both the behavioral variant of FTD and primaryprogressive aphasia, in which atrophy of the orbitofrontal and premotor areas was found to correlate with the occurrence of severely disabling behavioral changes (ie, aberrant eating and motor behaviors). [45][46][47] It is remarkable that no correlations were found between cortical thinning of the frontotemporal areas and frontal impairment (evaluated by T-score and subscores of FrSBe scale). By contrast, previous studies have reported an association between regional volume loss in several frontotemporal areas and cognitive and behavioral symptoms in both ALS 2,14,15,20 and the behavioral variant of FTD.…”
Section: Discussionmentioning
confidence: 99%
“…44 Moreover, the significant thinning of the orbitofrontal and premotor areas, which we found to correlate with ALSFRS-R and disease duration, may reflect a similar cortical degeneration pattern reported in both the behavioral variant of FTD and primaryprogressive aphasia, in which atrophy of the orbitofrontal and premotor areas was found to correlate with the occurrence of severely disabling behavioral changes (ie, aberrant eating and motor behaviors). [45][46][47] It is remarkable that no correlations were found between cortical thinning of the frontotemporal areas and frontal impairment (evaluated by T-score and subscores of FrSBe scale). By contrast, previous studies have reported an association between regional volume loss in several frontotemporal areas and cognitive and behavioral symptoms in both ALS 2,14,15,20 and the behavioral variant of FTD.…”
Section: Discussionmentioning
confidence: 99%
“…Visuospatial functioning also is relatively preserved, although there are some exceptions such as naPPA presenting in the context of CBS 58 . It is uncommon to observe a disorder of social functioning and personality early in the course ofnaPPA,although socially inappropriate behaviors seen in patients with behavioral variant FTD (bvFTD) can emerge over time, includingapathy, disinhibition or repetitive behaviors withlittle empathy and poor self-insight 59,60 . The nonlanguage spectrum of cognitive deficits in naPPA thus appears to involve limitations in working memory and executive control, but may implicate other cognitive and social domains particularly as the condition progresses.…”
Section: Other Cognitive Deficits In Nappamentioning
confidence: 99%
“…Recent studies have shown that patients with PNFA are not as functionally impaired as patients with AD [9], and that cognition is more affected than ADLs [11]. Behavioural disturbances are also present in patients with PNFA [12][13][14], although ADLs in PNFA, LPA and AD they were not reported as being significantly disturbing by their carers. There have been no studies of the impact of LPA on functional ability to date.…”
Section: Introductionmentioning
confidence: 98%